Vasopressors and Enteral Nutrition in the Survival Rate of Children During Extracorporeal Membrane Oxygenation. Issue 3 (1st June 2022) - Alexander, Erin; Absah, Imad; Steien, Dana B.; Grothe, Rayna; Crow, Sheri
Abstract : Objectives: Nutrition support is essential in improving outcome and survival in children on extra corporal membranous support (ECMO). We aim to evaluate the association between the timing of enteral nutrition (EN) initiation and its impact on outcome. Methods: We retrospectively reviewed the electronic health records of children (≤18 years) from November 2014 to November 2019 who were on veno-arterial ECMO for ≥48 hours. Abstracted data included demographics, ECMO indication and duration, timing of EN initiation, change in weight-for-age z score (WAZ), and survival rate. The vasoactive-inotropic score (VIS) was calculated to assess illness acuity. Results: We identified 76 children with median age (interquartile range [IQR]) of 0.3 years (0–2.6), 46 of which were infants (59%) who required ECMO for a median (IQR) of 10 days (6–22). Thirty-six (47%) survived to hospital discharge. EN was initiated in 55 (72%) of patients while on ECMO. EN initiation by day 3 of ECMO was positively associated with survival ( P = 0.0438). VIS at the time of EN initiation was lower in surviving infants ( P = 0.022). Children who achieved enteral autonomy were more likely to survive ( P = 0.0024). Survivors had greater WAZs at ECMO completion ( P = 0.0004). Conclusions: Initiation of EN by day 3 of ECMO and at a lower VIS is associated with greater likelihood of survival.